ERROR ANALYSIS OF ELEMENTRAY SCHOOL PRE-SERVICE TEACHER STUDENTS ON GEOMETRY LECTURES BASED NEWMAN THEORY - Mukmin, Muhammad Islahul (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
This study aims to describe the errors of elementary school pre-service teacher students in geometry lectures with the topic of triangles and congruence. This research used qualitative methode involving 33 PGMI students of State Islamic University of Malauna Malik Ibrahim Malang semester 3 in the 2023-2024 academic year. Researchers used Newman error analysis to explore the types of errors made by students in solving geometry problems. The results showed that most students experienced errors at the stage of understanding the problem, process transformation, process skills, and the stage of writing the final answer. Some subjects also still have errors in writing symbols.  This error is caused by the low conceptual understanding of students. Therefore, conceptual learning in geometrical concepts must be strengthened.